New Reactive Formulations For Polypropylene Foams. Issue 6 (12th April 2022) - Rainglet, Benoit; Verron, Lucas; Chalamet, Yvan; Bounor‐Legaré, Véronique; Delage, Karim; Forest, Charlène; Cassagnau, Philippe
Abstract: This work focuses on reactive extrusion to design polypropylene (PP) chains with long and short branching to obtain non‐linear behavior for the synthesis of low‐density foams (<100 kg m −3 ) using a batch supercritical carbon dioxide (scCO2 ) foaming process. From a maleic anhydride (MA) grafted PP (PP‐g‐MA), the long‐branched chains are performed using [MA]/ [OH] reaction (with Sorbitol alcohol). On the other hand, short branched chains are made from the hydrolysis/condensation of amino‐alkoxysilane (3‐Aminopropyl‐triethoxysilane, APTES) in situ grafted onto PP chains through the ([MA]/NH2 ] reaction). The results show the need to combine both systems to reach the optimum of the rheological behavior (linear and non‐linear) to obtain a low‐density foam. On the other hand, the foaming behavior of polypropylene/polyamide 6 (PP/PA6) polymer blends at T = 180 °C is also investigated as another way to control the rheology and foamy behavior. At this temperature, T = 180 °C, the PA6 phase behaves as solid dispersed particles in a viscoelastic liquid PP matrix. Finally, this study shows the influence of PA6 concentration on the foaming and foam morphology correlated to a rheological study (shear and extensional) and mechanical compressive properties. Abstract : Polypropylene chains with long and short branching are synthesized from PP‐g‐MA by reactive extrusion to obtain low‐density foams (<100 kg m −3 ) using a batch scCO2 foaming process. The foaming behavior at T = 180 °C of compatibilized PP/PA6 blends is also investigated as another way to control the foaming behavior and the resulting mechanical properties.